The design of the learning activities packages by using the learning technique on SQRC to develop grade 9 students’ reading, critical thinking and writing skills - Suwat, Madej (Universiti Malaysia Perlis, 2014)
Symposium of International Language & Knowledge (SiLK 2014), 14th-16th Feb 2014 was held at Hydro Hotel, Penang organized by Centre for International Languages, Universiti Malaysia Perlis.